Empirical Investigation of Service Quality and Students' Satisfaction in Higher Education - AsadMohi-ud-Din, Aysha Khalil, Atif Hassan (JCTE, 2023)
Higher educational institutions are able to gain students trust by treating them in equitable manner, handling their complaints in caring manner. Students' lives undergo a series of interrelated occurrence that persuades and overlies the student satisfaction. Thus, the main intention of this research was to comprehend the role of services quality in satisfaction of students with the value provided by their institutions, in return of what they have invested. This study also analyzes the difference between the satisfaction level of students of public and private universities towards quality of services. A standardized questionnaire to measure the higher education performance named HEdPERF,